Experimental investigation on strength properties of poly - propylene fibre reinforced concrete. Issue 1 (June 2020) - Jagan, D; Shankar, V; Sundara Mahalingam, T; Sathyan, Dhanya; Mini, K M; Sahai, Garvit
Abstract: The scope of the current investigation is to examine the mechanical properties of concrete with the addition of DURASTRAN Poly-propylene macro-fibres. The incorporation of highly engineered poly-propylene macro-fibre in concrete will result in improving many physical and mechanical properties of the concrete. Poly-propylene macro-fibre reinforced concrete has various applications such as tunneling & mining, commercial & industrial flooring and precast concrete structures. High strength (M40 grade) concrete with 0.36 water-cement ratio was used in this study. Poly-propylene macro-fibre was added only as an additional material, not as a replacement to aggregates. Various strength properties like compressive strength, tensile strength and flexural strength were studied and reported.